PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI MENGGUNAKAN PENDEKATAN KONTEKSTUAL - Markus, Daud; Halidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrak The purpose of this study is to describe the use of contextual component approach that can improve the ability to write essay writing essay students in the fourth grade of elementary school 04 Suak Bay Regency Bengkayang Regency. This study used a qualitative approach, the method used descriptive with the form of classroom action research (PTK) and collaborative. The place of research was conducted at State Elementary School 04 Teluk Suak Bengkayang Regency, class IV which amounted to 19 students with the subject of research teachers and students of grade IV. Data collecting technique used is observation technique, and document scrutiny technique with data collecting tool that is instrument assessment instrument of teacher ability to plan lesson, instrument sheet of teacher ability assessment to implement learning and document of student learning result.This research was conducted for 2 cycles with 2 meetings in each cycle. Assessment of learning implementation planning outcomes (RPP) from cycle I 3.05 and 3.09 increased by 0.02 and cycle II ie 3.50 and 3.71 increased by 0.21. Assessment of learning outcomes from cycles I 3.01 and 3.19 increased by 0.18 and cycle II ie 3.45 and 3.72 increased by 0.27. Assessment of writing result of narrative from cycle I 61,84 there are only 12 people complete while in cycle 100 all student complete. So students who complete from cycle I to cycle II is 100% Based on the data obtained can be concluded there is an increase in each cycle. Thus, the research using a contextual approach to learning to write essay writing class IV State Elementary School 04 Teluk Suak Bengkayang Regency can improve the skills of students writing narrative essay.Â Keywords: Improvement, Writing Narrative Writing, Contextual Approach